2016
DOI: 10.1158/1055-9965.epi-15-1096
|View full text |Cite
|
Sign up to set email alerts
|

Birth Size Characteristics and Risk of Brain Tumors in Early Adulthood: Results from a Swedish Cohort Study

Abstract: Background: Despite extensive research on the effect of birth size characteristics on childhood brain tumors, very few studies have evaluated the effect of birth size characteristics on the risk of adult brain tumor, and they have provided inconsistent results.Methods: All individuals born in Sweden between 1973 and 1995 who were still alive and cancer free at their 15th birthday were included in the study (n ¼ 2,032,727). At the end of the study period (December 31, 2010), the study participants were 15 to 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In addition, significant association of birth weight with prostate cancer risk compared to breast cancer risk in our results supports this statement. 6 Although multiple studies have shown associations between head circumference and the risk of brain, breast and colorectal cancer incidence, 23,24 we did not find any study assessing the association with cancer survival.…”
mentioning
confidence: 72%
“…In addition, significant association of birth weight with prostate cancer risk compared to breast cancer risk in our results supports this statement. 6 Although multiple studies have shown associations between head circumference and the risk of brain, breast and colorectal cancer incidence, 23,24 we did not find any study assessing the association with cancer survival.…”
mentioning
confidence: 72%
“…A meta-analysis of medium quality (46) found for neuroblastoma, an OR of 1.19 (95% CI 1.04-1.36) for birth weight >4,000 g compared with <4,000 g. The SR/meta-analysis (high quality) by Georgakis and co-workers in 2017 (47) reporting on all CNS tumors, found an OR of 1.14 (95% CI 1.08-1.20) for high birth weight and an OR of 1.12 (95% CI 1.03-1.22) for LGA. Two cohort studies, both with low risk of bias, found an association between high birth weight and CNS tumors (48,49), while one cohort study, with low risk of bias, found no association between LGA and CNS tumors (50). Nine out of 14 case-control studies had moderate risk of bias, where three studies (45,51,52) found an association between birth weight >4,000 g and CNS tumors, while six case-control studies, with moderate risk of bias, and one cross-sectional study (53) found no association.…”
Section: Cns Tumorsmentioning
confidence: 99%
“…Four studies examined the association of birth weight with risk of an adult CNS tumor [238,239,251,273]. Increasing birth weight (500 g-increment) was not associated with either overall CNS tumor risk (2 studies; OR: 0.99, 95%CI: 0.98-1.00; 1,091 cases) or glioma risk (3 studies; OR: 1.03, 95%CI: 0.98-1.07; 2,052 cases).…”
Section: Synthesis: Adult Cns Tumorsmentioning
confidence: 99%
“…Increasing birth weight (500 g-increment) was not associated with either overall CNS tumor risk (2 studies; OR: 0.99, 95%CI: 0.98-1.00; 1,091 cases) or glioma risk (3 studies; OR: 1.03, 95%CI: 0.98-1.07; 2,052 cases). Interestingly though, 2 studies [251,273] stratifying analyses by sex, reported male-restricted statistically significant associations of high birth weight with glioma.…”
Section: Synthesis: Adult Cns Tumorsmentioning
confidence: 99%
See 1 more Smart Citation